Effects of selenium and/or arbuscular mycorrhizal fungal inoculation on strawberry grown in hydroponic trial - Antoniou, Omiros; Chrysargyris, Antonios; Xylia, Panayiota; Tzortzakis, Nikos G. (My University, 2021)
Strawberry is considered as a fruit of high nutritional value, with appreciated benefits on human health. Arbuscular mycorrhizal fungi (AMF) are commonly used plant symbionts that affect plant growth and its effectiveness is plant species specific. Additionally, selenium (Se) projects a special interest to humans for its antioxidant specialties, and to plants, because of the potential to make them grow faster when added to the nutrient solution. Nonetheless, the performance of arbuscular mycorrhizal fungi (AMF) in Se biofortification in strawberry is unexplored. The purpose of the present study experiment was to determine whether mycorrhizal inoculation of AMF can have a positive impact on growth and quality of strawberries, and whether Se contributes in this effort or will adversely affect the plants. Four Se concentrations (0, 1, 5 and 10 mg L−1 ) in the nutrient solution, with or without mycorrhizal inoculation of AMF to the root system, were evaluated. Results demonstrated that Se of 10 mg L−1 negatively affected plant growth, photosynthetic rates, decreased fruit firmness and total soluble solids, induced oxidative stress in fruits and affected nutrient accumulation in different plant organs. Mycorrhizal inoculation of AMF mainly stimulated antioxidative mechanisms of the fruits and increased nutrient accumulation for plants grown at high Se levels. Based on our observations, mycorrhizal inoculation can enhance the nutritional value of strawberry fruits and strawberry plants seem to be a strong candidate for Se biofortification, allowing the rise of Se of the consumers’ intake.
Keywords: Fragaria ananassa; Selenium; Mycorrhizae; Health benefits; Hydroponics; Antioxidants; Symbiosis